Degradation of organic compounds in wastewater matrix by electrochemically generated reactive chlorine species: Kinetics and selectivity - Chung, Chong Min; Hong, Seok Won; Cho, Kangwoo; Hoffmann, Michael R. (ELSEVIER SCIENCE BV, 2018)
In this study, we examined the kinetics and selectivity of chemical oxygen demand (COD) degradation by electrochemically generated reactive oxygen species (RCS) in variable wastewater matrix. According to measurements on reactive oxidants and linear sweep voltammetry, oxidation of organics either via reactive oxygen species or direct electron transfer played a minor role for the active IrO2 anode. The RCS (mostly free chlorine in bulk solution) exclusively mediated an indirect oxidation with mean current efficiency from 25 to 40%. In batch galvanostatic experiments for single polymeric compounds, the rate of COD reduction showed marginal variations in spite of the large difference in reactivity with the RCS. Eight different wastewater samples were prepared from greywater and urine for potentiostatic experiments. The kinetics of COD degradation in municipal wastewater was observed to more sluggish than in the urinary samples with initial elevations in [COD]. Fractionation of COD into proteins, carbohydrates, and carboxylates could explain the shift in kinetics, in terms of the reactivity with RCS and the ratio of COD to theoretical oxygen demand (ThOD) for each components. The anaerobic biodegradation of the organic matrix greatly improved the subsequent reactivity with RCS, which rationalizes a combination of electrochemical processes with biological pretreatment.